Primary and secondary three-month outcomes of a cluster-randomized trial of home-based postpartum contraceptive delivery in southwest Trifinio, Guatemala - Harrison, Margo S. (Reprod Health, 2020)
DESIGN: This a cluster-randomized parallel arm pragmatic trial to observe the association of home-based postpartum contraceptive provision, including the contraceptive implant, with implant utilization rates at 3 months post-enrollment. METHODS: In a region of rural Guatemala referred to as the Southwest Trifinio, twelve communities are served by a community-based antenatal and postnatal care program. The communities were combined into eight clusters based on 2017 birth rates and randomized to receive the home-based contraceptive delivery (condoms, pills, injection, implant) during the routine 40-day postpartum visit. All participants receive comprehensive contraceptive counseling beginning at the first antenatal visit, so control clusters received this as part of routine care; this education preceded the study intervention. RESULTS: Once the 12 communities were combined into 8 clusters by expected birth volume and nurse team, which we expected to translate to eventual postpartum visits, the allocation sequence was generated in SAS. Of 208 women enrolled in the study, 108 were in four intervention and 100 in four control clusters. We used descriptive statistics to produce counts and percentages of characteristics of the study population overall and by intervention arm followed by univariate modeling using a mixed effects regression adjusted for cluster. Three-month contraceptive initiation rates were 56.0% in the control clusters compared to 76.8% in the intervention clusters, p < 0.001. Women in control clusters overwhelmingly opted for the injectable contraceptive (94.6%) while women in intervention clusters chose both the injection (61.5%) and the implant (33.7%), p < 0.001. Implant use by 3 months, the primary outcome of the study, was significantly higher in the intervention arm (25.9%) compared to the control arm (3.6%), p < 0.001, RR 1.3 CI [1.2, 1.4]. CONCLUSION: Our study was designed to respond to previously identified barriers to contraceptive uptake, and it was successful. Not only did it increase overall use of contraception by 3 months, but it shifted that contraceptive use away from short-acting methods in favor of longer-acting methods, with high continuation and satisfaction rates and no adverse outcomes reported. TRIAL REGISTRATION: clinicaltrials.gov, NCT04005391; Retrospectively Registered 7/2/2019,